Ultrastretchable Conductor Fabricated on Skin-Like Hydrogel-Elastomer Hybrid Substrates for Skin Electronics - Kim, Sun Hong; Jung, Sungmook; Yoon, In Seon; Lee, Chihak; Oh, Youngsu; Hong, Jae-Min (WILEY-V C H VERLAG GMBH, 2018)
Printing technology can be used for manufacturing stretchable electrodes, which represent essential parts of wearable devices requiring relatively high degrees of stretchability and conductivity. In this work, a strategy for fabricating printable and highly stretchable conductors are proposed by transferring printed Ag ink onto stretchable substrates comprising Ecoflex elastomer and tough hydrogel layers using a water-soluble tape. The elastic modulus of the produced hybrid film is close to that of the hydrogel layer, since the thickness of Ecoflex elastomer film coated on hydrogel is very thin (30 mu m). Moreover, the fabricated conductor on hybrid film is stretched up to 1780% strain. The described transfer method is simpler than other techniques utilizing elastomer stamps or sacrificial layers and enables application of printable electronics to the substrates with low elastic moduli (such as hydrogels). The integration of printed electronics with skin-like low-modulus substrates can be applied to make wearable devices more comfortable for human skin.
Keywords: ELASTIC CONDUCTORS; FILMS; RUBBER; THERAPY; SENSORS; DESIGN; FLAKES; INK